2022
DOI: 10.1021/acsenvironau.2c00015
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Multi-compartment Sampling for Quantification of Long-Term Accumulation of PAHs in Soils

Abstract: Long-term accumulation in the soils of ubiquitous organic pollutants such as many polycyclic aromatic hydrocarbons (PAHs) depends on deposition from the atmosphere, revolatilization, leaching, and degradation processes such as photolysis and biodegradation. Quantifying the phase distribution and fluxes of these compounds across environmental compartments is thus crucial to understand the long-term contaminant fate. The gasphase exchange between soil and atmosphere follows chemical fugacity gradients that can b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 76 publications
1
0
1
Order By: Relevance
“…Higher PAH air concentrations during autumn are likely a consequence of higher emissions from combustion during the cold seasons. Higher gaseous and air bulk deposition of PAHs during cold periods were also observed in Germany as a result of higher emission rates and higher load of particles containing higher air concentrations of PAHs in winter compared to summer [44]. The seasonal concentration pattern of PAHs has been previously described also in the Baltic Sea, where PAH concentrations in surface water [45] and air [46] were higher during cold periods.…”
Section: Sediment Pore-water Water and Air Concentrations Of Hocssupporting
confidence: 60%
See 1 more Smart Citation
“…Higher PAH air concentrations during autumn are likely a consequence of higher emissions from combustion during the cold seasons. Higher gaseous and air bulk deposition of PAHs during cold periods were also observed in Germany as a result of higher emission rates and higher load of particles containing higher air concentrations of PAHs in winter compared to summer [44]. The seasonal concentration pattern of PAHs has been previously described also in the Baltic Sea, where PAH concentrations in surface water [45] and air [46] were higher during cold periods.…”
Section: Sediment Pore-water Water and Air Concentrations Of Hocssupporting
confidence: 60%
“…S2 SI). Meierdierks et al [44] found that PAHs accumulated in soils were deposited from air almost exclusively during cold periods (> 80% of the annual deposition rates) [44]. In the current study, bulk deposition from air was not measured.…”
Section: Site-specific Sorption Of Hocscontrasting
confidence: 44%